Praiseworthiness of Dermatoglyphics in Determining Dental Caries Vulnerability among Gujarati Children: A Cross-Sectional Study - Chand, Sunil C; Parmar, Hardik R; Patel, Jayant Kumar L; Bathvar, Aeshha K; Garasiya, Nirav Kumar Z; Nisarta, Priyank Kumar K (National Journal of Community Medicine, 2018)
Introduction: Dermatoglyphics is the study of finger prints from toes, fingers palms, and soles of animals and humans. Der- matoglyphic examination is opening up as an exceptionally tool for initial investigations into circumstances with an alleged genetic basis. The current study was conducted to determine worthiness of dermatoglyphics in prophesying genetic vulnerability of chil- dren to dental caries via cost-effective means. Materials and Methods: Cross-sectional study was undertaken on 100 children of age group between 4–14 years divided equally into two groups namely: Caries-free group (def/DMF score “0”) and Caries group (def/DMF score more than or equal to “5”). Both were subdivided into 25 males and 25 females. Each child’s hand- prints were taken and observed for dermatoglyphic pattern; total finger ridge count TFRc and atd angle. Results: Whorls were found more in caries group whereas ulnar loops were more common in caries free group. Total finger ridge count was significantly higher in caries group. The atd angles did not show any significant differences among caries and caries free group. Conclusion: Dermatoglyphic pattern variation may be an impor- tant tool in identification of people at risk of developing dental caries, which will enable an early detection and prevention of the disease.